Transrectal decompression as a new approach for treatment of large intestinal tympany in horses with colic: Preliminary results. (20th August 2012) - Scotti, G. B.; Lazzaretti, S. S.; Zani, D. D.; Magri, M.
Summary A common feature of colic in horses is tympany in the large intestine and medical treatment of this condition can be unsuccessful. In this article we describe and evaluate a new approach for decompression of large intestinal tympany in equine colic patients using transrectal puncture. We evaluated horses showing colic symptoms and colonic or caecal tympany and the final diagnosis, complications and final outcome were recorded for each horse. A special transrectal decompression device (TDD) was developed and used to perform transrectal decompression (TD) by gas aspiration. In order to assess pain reduction as a result of TD, heart rate (HR) was recorded before and after the decompression procedure. Twenty‐five horses were included in the study. In 17 cases, tympany was recognised as primary in origin while in 8 it was secondary to other conditions. A total of 33 TDs were performed and no horses developed short‐ or long‐term complications. All horses were alive after the first month post TD, while 5 died from diseases not related to TD. The TD could safely and easily be performed in all horses presenting tympany. Transrectal decompression can easily be performed, 2 or even 3 times to treat a single colic episode by using the transrectal device connected to a surgical aspirator. It was not possible from available information to relate the timing of HR decrease to resolution of colic or to administration of drugs because a retrospective study and all such data were not readily accessible. Our clinical results support the relevance of the TD as an elective treatment of primary large intestinal tympany, emergency treatment of tympany secondary to other surgical entities and as palliative treatment in surgical patients, in which surgery could not be achieved.